Implementasi Media Promosi Produk Home Industry di Kabupaten Agam dan Lima Puluh Kota - Almukarrom Ramadhan, Sayyid Barqi; Annas, Firdaus; Henra, Raseb (Yayasan Lembaga Studi Makwa, 2025)
This research aims to analyze and implement OperCart as a promotional media for home industry products in Agam and Lima Puluh Kota Regencies. This research is expected to increase market access and competitiveness of local products through the use of digital technology. Currently, home industries in the Agam and Lima Puluh Kota Regencies face various obstacles, such as limited access to a wider market, lack of effective promotional media, and the low level of adoption of digital technology by business actors. By utilizing digital technology such as OperCart, businesses can promote products more efficiently, reach a wider market, and increase competitiveness in the midst of global competition. This research uses a descriptive approach with a system development method. The research stages include needs analysis, OperCart design and implementation, and platform performance evaluation through interviews, surveys, and direct observation of users. The implementation of OperCart showed a significant increase in the effectiveness of home industry product promotion. Within three months of use, the platform managed to increase sales transactions by 40% and expand market reach by 55%. Businesses responded positively to OperCart because of its ease of use and features that support promotional needs, such as product catalogs, transaction recording, and social media integration. This research proves that digital platforms such as OperCart can be an effective solution to improve the competitiveness of home industries. Further development recommendations include the addition of marketing analytics features and technical training for businesses to optimize the use of the platform.